The Relationship of Alcohol Use Disorders and Depressive Symptoms to Tryptophan Metabolism: Cross-Sectional Data from a Nepalese Alcohol Treatment Sample - Neupane, Sudan Prasad; Lien, Lars; Martinez, Priscilla; Hestad, Knut; Bramness, Jørgen G. (Alcoholism, clinical and experimental research, 2015)
Background Activation of the kynurenine pathway of tryptophan metabolism results in increased production of potentially depressogenic tryptophan catabolites and a reduction in tryptophan availability for serotonin synthesis. As alcohol consumption affects tryptophan metabolism and disposition, we determined serum levels of tryptophan, kynurenine, and an index of tryptophan degradation (kynurenine/tryptophan ratio) in patients with alcohol‐use disorder (AUD) and compared their levels considering abstinence duration, AUD severity, and comorbid depression. Methods The study sample included 169 AUD inpatients from 8 alcohol treatment facilities in Kathmandu, Nepal. The Composite International Diagnostic Interview was administered to generate the AUD diagnosis. The Alcohol Use Disorder Identification Test (AUDIT) captured AUD severity and patterns of alcohol use. The Hopkins Symptom Checklist‐25 was used to reveal current depressive symptoms. Serum kynurenine and tryptophan levels were determined by high‐performance liquid chromatography, and tryptophan degradation was measured by KT ratio (kynurenine/tryptophan × 103). Results Patients with above average AUDIT scores had higher mean serum levels of kynurenine (2.1 μM ± 0.7 vs. 1.8 μM ± 0.6, p = 0.006) and KT ratios (48.6 ± 17.6 vs. 40.4 ± 14.3, p = 0.002) than those with below average scores. Patients with current depressive symptoms had higher mean tryptophan concentrations (49.9 μM ± 13 vs. 45.7 μM ± 14.1, p = 0.047) and lower KT ratios (41.4 ± 14 vs. 47.5 ± 17.6, p = 0.028) compared to patients whose reported depressive symptoms were below the standard cutoff. Higher tryptophan levels and lower KT ratios in the depressed group were specific to patients with longer abstinence and higher AUD severity. Conclusions Depression‐related deregulation in tryptophan metabolism was found to depend on length of abstinence and on AUD severity. Together, results suggest that in AUD populations, peripheral tryptophan metabolism is subject to interactions between AUD severity and depressive symptoms.